The NuSTAR extragalactic survey of the James Webb Space Telescope North Ecliptic Pole time-domain field. Issue 4 (6th October 2021) - Zhao, X; Civano, F; Fornasini, F M; Alexander, D M; Cappelluti, N; Chen, C T; Cohen, S H; Elvis, M; Gandhi, P; Grogin, N A; Hickox, R C; Jansen, R A; et al.
ABSTRACT: We present the NuSTAR extragalactic survey of the James Webb Space Telescope ( JWST ) North Ecliptic Pole (NEP) Time-Domain Field. The survey covers a ∼0.16 deg 2 area with a total exposure of 681 ks acquired in a total of nine observations from three epochs. The survey sensitivities at 20 per cent of the area are 2.39, 1.14, 2.76, 1.52, and 5.20 × 10 −14 erg cm −2 s −1 in the 3–24, 3–8, 8–24, 8–16, and 16–24 keV bands, respectively. The NEP survey is one of the most sensitive extragalactic surveys with NuSTAR so far. A total of 33 sources were detected above 95 per cent reliability in at least one of the five bands. We present the number counts, log N -log S, measured in the hard X-ray 8–24 and 8–16 keV bands, uniquely accessible by NuSTAR down to such faint fluxes. We performed source detection on the XMM – Newton and Chandra observations of the same field to search for soft X-ray counterparts of each NuSTAR detection. The soft band positions were used to identify optical and infrared associations. We present the X-ray properties (hardness ratio and luminosity) and optical-to-X-ray properties of the detected sources. The measured fraction of candidate Compton-thick ( N _H10^24 cm^-2 ) active galactic nuclei, derived from the hardness ratio, is between 3 and 27 per cent. As this survey was designed to have variability as its primary focus, we present preliminary results on multiepoch flux variability in the 3–24 keV band.